An Exploration Of Facilitators And Barriers Of Work Engagement Among Private Sector Workers - Syamilia Nurin, Shamsuddin (Universiti Malaysia Sarawak (UNIMAS), 2021)
There are rapid changes in the world of work in many aspects. Employees who are the important asset in an organization contribute to its success and achievement. In light of the concerns, employees need to adapt with the changes involving their task in order to be engaged. This study attempts to explore and identified the facilitators and barriers of work engagement of employees working in private sectors. While the significant attention has been made on the concept of work engagement, there were few gaps in this study particularly in less study in Malaysia and its methodology. The research design used is qualitative case study in qualitative approach. The study was conducted in Kuching, Sarawak. The data were collected from 8 respondents which were employed in private sectors which were coming private institution and private automotive industry The data were collected using a semistructured interview and audio recorded. Content analysis was used for data analysis procedure. It was found that passion, support received working environment and condition, learning and development initiatives, and rewards and recognition are the major facilitators in employees’ work engagement. Meanwhile, the barriers discovered were personal characteristics (laziness, boredom, not feeling positive, and delaying works), work-related factors (new changes at workplace, and working condition), and personal problems. Finally, summarization, implication, and recommendation for this study are also further elaborated to gives insight and awareness as well as providing measures for the barriers at work.